A Divergent Approach for the Synthesis of d- and l-4′-Ethynyl Dioxolane Nucleosides with Potent Anti-HIV Activity - Singh, Sarbjit; Gajulapati, Veeraswamy; Kim, Minkyoung; Goo, Ja-Il; Lee, Jae Kyun; Lee, Kyeong; Lee, Chong-Kyo; Jeong, Lak Shin; Choi, Yongseok (Synthesis, 2016)
Novel 4′-C-ethynyl isomeric dioxolane nucleoside analogues (β-d, α-d, β-l, and α-l, respectively) are successfully synthesized via a divergent strategy from the common starting material, (Z)-but-2-ene-1,4-diol, and are characterized and evaluated for their anti-HIV-1 and anti-HIV-2 activities. The β-d and β-l products display potent in vitro activities against HIV-1 (IIIB) with EC50 values of 0.75 and 0.87 μM, respectively, and against HIV-2 (ROD) with EC50 values of 0.75 and 0.35 μM, respectively, being better in comparison with 3TC [EC50, 5.27 μM (HIV-1) and 1.30 μM (HIV-2)]. The β-d and β-l nucleosides also potently inhibit different drug-resistant strains of the HIV-1 virus (L100I, K103N, Y181C, and V106A). The selectivity indices and cytotoxic profiles of the β-d and β-l nucleosides are much better than those of the standard drugs AZT and d4T.
Keywords: anti-HIV; AIDS; dioxolane nucleosides; 4′-acetylene nucleosides; divergent synthesis; asymmetric synthesis